STUDENT ACTIVITIES IN DIFFERENTIATED MATHEMATICS LEARNING WITH THE TEACHING AT THE RIGHT LEVEL (TARL) APPROACH - Utami, Tia; Neneng Aminah; Wendi Kusriandi; Hapsari, Trusti (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study aims to describe the activity implementation of the Teaching at the Right Level (TaRL) approach through differentiated learning in Mathematics subject matter statistics in class VIII. This research is included in qualitative descriptive research. The data sources used in this study are the learning process, mathematics teacher informants, documents related to Teaching at the Right Level (TaRL) through differentiated learning, and field notes on the learning process using the Teaching at the Right Level (TaRL) approach through differentiated learning. Data collection techniques were observation, and document analysis. The results of this study show that the implementation of the Teaching at the Right Level (TaRL) approach through differentiated learning is in accordance with the stages of the Teaching at the Right Level (TaRL) approach, namely classifying the learning needs of students, developing differentiated learning designs and implementation, and reflecting and evaluating learning.